(untitled) (Jurnal Simki Economic, 2024)
This study aims to investigate whether understanding in accounting can be affected by learning behavior patterns. In addition, this study also aims to identify a possible relationship between learning behavior patterns and the level of understanding in accounting, taking into account the moderating effect of emotional intelligence. The method used in this study was convenience sampling, with a total sample of 86 respondents who were students of the Accounting study program at Sarjaniwiyata Tamansiswa University. The data taken for this study is primary data obtained through a questionnaire containing the responses from the respondents. The analysis technique applied is path analysis, where learning behavior serves as the independent variable, the level of understanding of accounting as the dependent variable, and emotional intelligence as the moderator variable. The results of the analysis show that learning behavior has the potential to influence the level of understanding of accounting. In addition, emotional intelligence also has the potential to moderate the influence between learning behavior and learning interest on the level of understanding of accounting. This finding has important implications in the context of this research.